To suppress tin whisker growth by using (100)-oriented copper - Lin, Han-Wen; Lu, Jia-Ling; Hu, Chih-Chia; Tu, K.N.; Chen, Chih (Journal of materials research and technology, 2025)
Effect of Cu crystallographic orientations on the Sn whisker growth is investigated in this study. Three types of Cu under-layer (randomly, , -oriented) were prepared for electroplating of pure Sn. After 672 h of room temperature (RT) storage, a lot of whiskers were found on the Sn surface electroplated on the randomly-oriented Cu, whereas very few whiskers can be seen on those electroplated on the − or the -oriented Cu. It is also found that the behavior of intermetallic compound (IMC) growth at the Sn–Cu interface is quite different between the randomly- and specifically-oriented Cu films, which leads to divergent phenomena of Sn whisker growth. Furthermore, after 7944 h of RT storage, both the − and the -oriented Cu films are proven to be effective on preventing Sn whisker growth. Orientation analysis indicated the Sn grains on the − and the -oriented Cu possesses preferred orientation, which may slow down the formation of the Cu–Sn IMCs.